Spatial–Temporal Heterogeneity of Wetlands in the Alpine Mountains of the Shule River Basin on the Northeastern Edge of the Qinghai–Tibet Plateau - Shuya Tai; Donghui Shangguan; Jinkui Wu; Rongjun Wang; Da Li (Remote Sensing)
Alpine wetland ecosystems, as important carbon sinks and water conservation areas, possess unique ecological functions. Driven by climate change and human activities, the spatial distribution changes in alpine wetlands directly affect the ecosystems and water resource management within a basin. To further refine the evolution processes of different types of alpine wetlands in different zones of a basin, this study combined multiple field surveys, unmanned aerial vehicle (UAV) flights, and high-resolution images. Based on the Google Earth Engine (GEE) cloud platform, we constructed a Random Forest model to identify and extract alpine wetlands in the Shule River Basin over a long-term period from 1987 to 2021. The results indicated that the accuracy of the extraction based on this method exceeded 90%; the main wetland types are marsh, swamp meadow, and river and lake water bodies; and the spatial–temporal distribution of each wetland type has obvious heterogeneity. In total, 90% of the swamp meadows areas were mainly scattered throughout the study area’s section 3700 to 4300 m above sea level (a.s.l.), and 80% of the marshes areas were concentrated in the Dang River source 3200 m above sea level. From 1987 to 2021, the alpine wetland in the study area showed an overall expansion trend. The total area of the wetland increased by 51,451.8 ha and the area increased by 53.5%. However, this expansion mainly occurred in the elevation zone below 4000 m after 2004, and low-altitude marsh wetland primarily dominated the expansion. The analysis of the spatial–temporal heterogeneity of alpine wetlands can provide a scientific basis for the attribution analysis of the change in alpine wetlands in inland water conservation areas, as well as for protection and rational development and utilization, and promote the healthy development of ecological environments in nature reserves.